Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, 315+(125-x)=435
<=> 125 - x = 435 - 315
<=> 125 - x = 120
<=> x = 5
b, 6x-5=613
<=> 6x = 613 + 5
<=> 6x = 618
<=> x = 103
c, 128-3(x+4)=23
<=> 3(x +4 ) = 105
<=> x + 4 = 35
<=> x = 31
e, -x +8=17
<=> x = -9
a, 315+(125-x)=435
125-x=435-315=120
x=125-120=5
=>x=5
b,6x-5=613
6x=613+5=618
x=618:6=103
c, 128-3(x+4)=23
3(x+4)=128-23=105
x-4=105:3=35
x=35+4=39
Ý D NHẦM ĐẦU BÀI BẠN ƠI.
\(3x^2-2x-8=0\\ \Leftrightarrow3x^2-2x=8\\ E=6x^2-4x+9\\ =3x^2+3x^2-2x-2x-8+17\\ =\left(3x^2-2x-8\right)+\left(3x^2-2x+17\right)\\ =3x^2-2x+17\\ =\left(3x^2-2x\right)+17=8+17=25\)
\(x+y=0\\ \Leftrightarrow y=-x\\ D=x^4-y^4+x^3y-xy^3\\ =\left(x^2+y^2\right)\left(x^2-y^2\right)+xy\left(x^2-y^2\right)\\ =\left(x^2+y^2+xy\right)\left(x^2-y^2\right)\\ =\left(x^2+\left(-x\right)^2+x.\left(-x\right)\right)\left(x^2-\left(-x\right)^2\right)\\ =\left(x^2+x^2-x^2\right)\left(x^2-x^2\right)\\ =x^2.0=0\)